2018
DOI: 10.1097/md.0000000000011982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gene expression profile and DNA methylation status in diabetic patients of Kazak and Han people

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Results from case-control EWAS Illumina-array based studies yielded very heterogeneous findings, likely reflecting the sex, fat depot and age-related differences between cohorts ( Table 2 and Supplementary Table 3 ). In total, several thousand DMRs were identified in the AT of individuals that had MUHO, although without significant overlap between the individual studies ( 60 65 , 68 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from case-control EWAS Illumina-array based studies yielded very heterogeneous findings, likely reflecting the sex, fat depot and age-related differences between cohorts ( Table 2 and Supplementary Table 3 ). In total, several thousand DMRs were identified in the AT of individuals that had MUHO, although without significant overlap between the individual studies ( 60 65 , 68 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the 23 papers included in this systematic review, 19 papers reported studies on DNA methylation, 2 papers presented data on histone modifications and 2 papers conducted studies on lncRNAs. Of the 19 papers that reported data on DNA methylation in AT from individuals with MUHO, 8 papers performed targeted epigenome studies (52-59) and 11 papers reported genome-wide studies (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). The main findings on the targeted DNA methylation studies are summarized in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Given the largely medical nature of the reviewed literature, an emphasis on pathology is predominant, and exposures are generally understood exclusively in the negative, that is, as a source of risk for chronic disease and mortality and dysfunction of biological processes (Agha et al, 2016 ; Chan et al, 2017 ; de Mendoza et al, 2018 ; Do et al, 2021 ; Kader et al, 2020 ; Jhun et al, 2021 ; Lara et al, 2020 ; Lapato et al, 2018 ; Needham et al, 2015 ; Pheiffher et al, 2020; Rizzo et al, 2020 ; Tekola‐Ayele et al, 2020 ; Tehranifar et al, 2018 ; Wang et al, 2018 ; Tsegaselassie et al, 2021 ; Zhu et al, 2016 ).…”
Section: A Scoping Review Of Environmental Epigenetics Dohad and Race...mentioning
confidence: 99%
“…The upregulated genes were associated with fatty acid and carbon metabolism. It seems interesting that, despite the presence of many common networks, the genetic patterns differ in the Han and Kazak Chinese patients, which allows for conclusions to be drawn about the differences in the gene expression in different populations [ 26 ]. The overexpression of the HLA-DQA1 and HLA-DQB1 genes encoding subunits of MHC class II molecules, which are responsible for antigen presentation by immune cells, was demonstrated in T2D individuals, proving the commonality of immune response activation in T1D, T2D, and latent autoimmune diabetes in adults.…”
Section: Transcriptome Studies In T2dmentioning
confidence: 99%